A 0D Lead‐Free Hybrid Crystal with Ultralow Thermal Conductivity. (7th February 2019) - Haque, Md Azimul; Gandi, Appala Naidu; Mohanraman, Rajeshkumar; Weng, Yakui; Davaasuren, Bambar; Emwas, Abdul‐Hamid; Combe, Craig; Baran, Derya; Rothenberger, Alexander; Schwingenschlögl, Udo; Alshareef, Husam N.; Dong, Shuai; et al.
Abstract: Organic–inorganic hybrid materials are of significant interest owing to their diverse applications ranging from photovoltaics and electronics to catalysis. Control over the organic and inorganic components offers flexibility through tuning their chemical and physical properties. Herein, it is reported that a new organic–inorganic hybrid, [Mn(C2 H6 OS)6 ]I4, with linear tetraiodide anions exhibit an ultralow thermal conductivity of 0.15 ± 0.01 W m −1 K −1 at room temperature, which is among the lowest values reported for organic–inorganic hybrid materials. Interestingly, the hybrid compound has a unique 0D structure, which extends into 3D supramolecular frameworks through nonclassical hydrogen bonding. Phonon band structure calculations reveal that low group velocities and localization of vibrational energy underlie the observed ultralow thermal conductivity, which could serve as a general principle to design novel thermal management materials. Abstract : Intriguing physical and chemical properties of a 0D organic–inorganic hybrid crystal lead to unique thermal transport. Ultralow thermal conducti‐vity of 0.15 W m −1 K −1 is recorded for [Mn(C2 H6 OS)6 ]I4 owing to its 0D structure and localization of vibrational energy.